The Role of the Internet in Facilitating Violent Extremism: Insights from Former Right-Wing Extremists - Gaudette, Tiana (Terrorism and political violence, 2022)
While a growing body of evidence suggests that the Internet is a key facilitator of violent extremism, research in this area has rarely incorporated former extremists’ experiences with the Internet when they were involved in violent extremism. To address this gap, in-depth interviews were conducted with ten Canadian former right-wing extremists who were involved in violent racist skinhead groups, with interview questions provided by thirty Canadian law enforcement officials and ten community activists. Participants were asked about their use of the Internet and the connection between their on- and offline worlds during their involvement in the violent right-wing extremist movement. Overall, our study findings highlight the interplay between the Internet and violent extremism as well as the interactions between the on- and offline worlds of violent extremists. We conclude with a discussion of study limitations and avenues for future research.